Gagasan Integrasi Nilai-Nilai Adat Basandi Syarak Syarak Basandi Kitabullah (ABS SBK) Kedalam Pelajaran Pendidikan Agama Islam Pada Kurikulum Sekolah Dasar - Albert Albert; Iswantir Iswantir; Fauzan Ismail; Zainir Zainir (Jurnal Pendidikan Indonesia, 2022)
the curriculum in a broad sense needs to be continuously criticized. In this case, a formulation of PBM activities is needed that does not separate the science, skills and cultural values of the local community. This paper explains the idea of a formulation of the integration of Minangkabau cultural values which is contained in the adagium "Adat Basandi Syarak Syarak Basandi Kitabullah" (ABS SBK) into the curriculum of Islamic Religious Education (PAI) in elementary schools. This integration formulation is carried out as a solution to various kinds of social and moral problems faced by the world of education in the face of the wave of modernization. In addition, it can be believed that the values of "Adat Basandi Syarak Syarak Basandi Kitabullah" are an adagium that becomes the system of life of the people of West Sumatra (Minangkabau) which is based on Islamic religious values (Quran and Hadith of Prophet Muhammad SAW). The purpose of this study was to formulate the idea of ​​an integrated curriculum in the perspective of Minangkabau socio-cultural, adat basandi syarak syarak basandi Kitabullah into Islamic religious education subjects in the basic segolah curriculum. The research method is library research with a descriptive qualitative approach. The results of the study show that the traditional values ​​of basandi syarak syarak basandi Kitabullah can be integrated into Islamic religious education lessons in the elementary school curriculum through a process of integration and interconnection by strengthening the organization of curriculum content.